Developments in Health Monitoring of Civil Structures: Sensors and IoT Applications - Santosh Kumar, Gottapu (International Journal of Psychosocial Rehabilitation, 2020)
The increasing need for resilient and sustainable infrastructure has fueled advancements in health monitoring of civil structures. This research paper explores the integration of sensors and Internet of Things (IoT) technologies in monitoring the health of such structures. The introduction provides a context for the significance of health monitoring in ensuring the longevity and safety of infrastructure. A comprehensive literature review delves into existing studies, highlighting the diverse array of sensors used in structural health monitoring and discussing IoT applications. The paper categorizes and analyzes various sensors, such as accelerometers, strain gauges, and displacement sensors, elucidating their principles of operation and respective advantages and limitations. It further explores the role of IoT in structural health monitoring, emphasizing real-time data acquisition, transmission, storage, and analysis. Case studies are presented to illustrate successful implementations of sensor and IoT technologies in diverse scenarios, providing insights into their practical applications and outcomes. Challenges and opportunities in the field are discussed, including issues related to data security and privacy. The paper concludes by outlining future directions, anticipating emerging trends, and suggesting areas for further research. This comprehensive exploration contributes to the growing body of knowledge in structural health monitoring, guiding researchers and practitioners toward more robust and efficient monitoring solutions for civil structures.